33.8k views
2 votes
Linda and Roy are solving the equation 4x+3x-7=(1+4x)+5x. Linda uses a first step that results in 4x+7-3x=(1+4x)+5x Roy uses a first step that results in 4x+3x-7=1+(4x+5x) which statement about the first steps Linda and Roy use is true

Linda and Roy are solving the equation 4x+3x-7=(1+4x)+5x. Linda uses a first step-example-1
User Hardiksa
by
5.3k points

1 Answer

4 votes

Answer:

Option C

Explanation:

Linda used the first step that results in,

4x + 7 - 3x = (1 + 4x) + 5x

As Linda changed the sign of (3x) to (-3x), it doesn't matches the original equation.

So she is not correct.

Roy used the first step as,

4x + 3x - 7 = 1 + (4x + 5x)

He has used the associative property in the right hand side of the given equation.

Associative property → (a + b) + c → a + (b + c)

Therefore, he is correct.

Option C is the correct option.